Computational Insight into Calcium-Sulfate Ion Pair Formation - Byrne, E.; Raiteri, Paolo; Gale, Julian (American Chemical Society, 2017)
© 2017 American Chemical Society. The thermodynamics of ion pair formation between Ca 2+ and SO 4 2- has been studied using a rigid ion force field, the polarizable AMOEBA force field, and ab initio molecular dynamics simulation. The results obtained from the three methods are remarkably similar and consistent with the available experimental data and show that the ion association is driven by an increase in entropy, which can be related to the release of water molecules as previously found for Ca 2+ and CO 3 2- . Two new rigid ion force fields targeting different solvation free energies for sulfate have been developed. The comparison between static and dynamic properties of the solvated anion, as well as the pairing free energy with Ca 2+ , suggest that the model with the strongest solvation is more realistic, which may help to resolve the inconsistency in the current literature.